(untitled) (The Pakistan Development Review, 1999)
Education has positive links with economic development as it raises the productivity of the work force. Beside private rates of returns, the social returns of education are also high. Because of the gains to society, education is subsidised in many countries. Pakistan, where only 2.5 percent of the GDP is spent on education, provides subsidised education in the form of a public school system.1 Government pays for the major expenditures such as construction of infrastructure for education and salaries to the teaching and related staff. Household cost is kept low to attract more people to send their children to schools. Therefore only a nominal tuition fee is being charged for attending these schools.